Land use and soil characteristics affect soil organisms differently from above-ground assemblages - Burton, Victoria J.; Contu, Sara; De Palma, Adriana; Hill, Samantha L. L.; Albrecht, Harald; Bone, James S.; Carpenter, Daniel; Corstanje, Ronald; De Smedt, Pallieter; Farrell, Mark; Ford, Helen V.; Hudson, Lawrence N.; et al. (BioMed Central, 2022)
Background: Land-use is a major driver of changes in biodiversity worldwide, but studies have overwhelmingly focused on above-ground taxa: the effects on soil biodiversity are less well known, despite the importance of soil organisms in ecosystem functioning. We modelled data from a global biodiversity database to compare how the abundance of soil-dwelling and above-ground organisms responded to land use and soil properties. Results: We found that land use affects overall abundance differently in soil and above-ground assemblages. The abundance of soil organisms was markedly lower in cropland and plantation habitats than in primary vegetation and pasture. Soil properties influenced the abundance of soil biota in ways that differed among land uses, suggesting they shape both abundance and its response to land use. Conclusions: Our results caution against assuming models or indicators derived from above-ground data can apply to soil assemblages and highlight the potential value of incorporating soil properties into biodiversity models.
Keywords: Land-use; Land-use intensity; Soil biota; Soil biodiversity; Organism abundance; Mixed-effects models